Long-term persistence of oral human papillomavirus type 16: The HPV Infection in Men (HIM) Study - Campbell, Christine M. Pierce (Cancer Prev Res (Phila), 2015)
Persistent infection with oral HPV16 is believed to drive the development of most oropharyngeal cancers. However, patterns of oral HPV16 persistence remain understudied, particularly among HIV-negative individuals. Oral HPV16 persistence was evaluated among 1626 participants of the HPV Infection in Men (HIM) Study. Twenty-three oral HPV16-positive men who provided an oral gargle sample on ≥2 study visits were included in the analysis. Archived oral samples from all follow-up visits were tested for HPV16 using Linear Array and INNO-LiPA detection methods. Persistence was evaluated using consecutive HPV16-positive visits held approximately 6 months apart and using the Kaplan-Meier method. Oral HPV16-positive men were aged 18–64 years (median, 36 years; IQR, 25–42) and were followed for a median of 44.4 months (IQR, 29.9–49.5). Of 13 incident infections, 4 (30.8%) persisted ≥12 months, 1 (10.0%) persisted ≥24 months, and none persisted ≥36 months (median infection duration, 7.3 months [95% CI, 6.4–NA]). Of 10 prevalent infections, 9 (90.0%) persisted ≥12 months, 8 (80.0%) persisted ≥24 months, 4 (57.1%) persisted ≥36 months, and 2 (40.0%) persisted ≥48 months (median infection duration, NA). Twelve-month persistence of incident infections increased significantly with age (P trend=0.028). Prevalent oral HPV16 infections in men persisted longer than newly acquired infections, and persistence appeared to increase with age. These findings may explain the high prevalence of oral HPV observed at older ages. Understanding oral HPV16 persistence will aid in the identification of men at high-risk of developing HPV-related oropharyngeal cancer.